INOVASI PEMANFAATAN SAMPAH PLASTIK MENJADI ECO-BRICK : STRATEGI PENINGKATAN KESADARAN LINGKUNGAN MASYARAKAT DI DESA BAGIK MANIS - Joniarta, I Wayan; Aljibran, Aljibran; Fitrirayani, Gadis Ariva; Rohayani, Tri Sari; Rifki, Lalu Muhammad; Febriyawan, Gilang; Putri, Ghea Sabina Anggia; Astiani, Arbiatun; Hartati, Dea Rara; Supaerina, Eji; Putri , Sarina Adila (Jurusan Teknik Elektro Universitas Mataram, 2025)
The phenomenon of plastic waste pollution has become a serious problem both globally and nationally, including in Bagik Manis Village, East Lombok Regency. Low public awareness of waste management has prompted students participating in the Community Service Program (KKN PMD) at Mataram University to implement an environmental education program that utilizes plastic waste to make eco-bricks. This study employed survey, interview, observation, and direct practice methods, including waste sorting, outreach, and eco-brick production. The results show an increase in public awareness of waste management, as evidenced by the increase in the number of residents using the village waste collection service from around 50 people to 80-90 people, as well as the involvement of 10 people in the practice of making eco-bricks, which were turned into benches and cushions. This program not only has an impact on reducing the volume of plastic waste, but also opens up economic opportunities through environmentally friendly products.